TECHNOLOGICAL ASPECTS OF PRODUCTION OF EPOXY ASPHALT CONCRETE BY ADDING CARBON ADDITIVES - Atynian, A.; Butnik, S.; Hovorukha, I. (Municipal economy of cities (Technical science), 2024)
Epoxy asphalt concrete is a durable, high-quality material consisting of epoxy resins, hardeners, and the mineral part itself. Accordingly, slow-hardening epoxy asphalt concrete has high physical properties and low sensitivity to temperature changes, which makes it usable as a rigid pavement and applicable even on metal and concrete bridge decks. However, a downside of epoxy asphalt concrete is its ability to gain strength over a long period of operation (up to 1 year). It is a disadvantage when using such coatings in the upper layer of the road surface. In addition, a long period of strength gain during intensive use of the road pavement leads to critical destruction of the pavement itself, plastic deformation, and a reduction in the service life (which may differ much from the standard). Using metal fibre substantially increases the strength and keeps the area from collapsing. The use of metal elements can significantly reduce the performance of the tires of vehicles that will drive on the road and even create a hazard in the event of destruction of the epoxy asphalt concrete area. Using epoxy binders notably increases the strength characteristics of road materials, especially at high temperatures, and boosts their ability to resist rutting. At the same time, the characteristics of epoxy concrete do not decrease during operation and at low temperatures, which indicates the versatility of such a material. The only drawback that cancels out all the positive features of epoxy asphalt concrete is its long strength gain. This disadvantage not only led to the problems mentioned above but also delayed the opening of traffic, which, especially on roads of higher categories, caused traffic disruption and inconvenience to the movement of vehicles. The authors proposed a solution to this problem by developing an improved epoxy asphalt concrete composition by introducing fibre ash into the developed composition as a reinforcing and structuring additive that accelerates the pavement formation time and strengthens the asphalt matrix in epoxy asphalt concrete.